2014
DOI: 10.1155/2014/935379
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Incidence and Clinical Features of Antibody-Associated Autoimmune Encephalitis Mimicking Dementia

Abstract: Background. Anti-neuronal autoimmunity may cause cognitive impairment that meets the criteria for dementia. Objective. Our aim was to detect the incidence and clinical features of autoimmune encephalitis imitating clinical findings of primary dementia disorders and to delineate the validity of anti-neuronal antibody screening in dementia patients. Methods. Fifty consecutive patients fulfilling the clinical criteria for primary dementia, 130 control patients, and 50 healthy controls were included. Their sera we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 15 publications
(25 reference statements)
1
44
0
Order By: Relevance
“…Results have been less compelling for anti-AMPAR antibodies, as the majority of studies have been negative [10, 15, 18, 20, 23, 26, 28, 29]. Moreover, in each of the two positive studies, antibodies were found in only one patient (<1% of the samples) [11, 24], and the only study that included a healthy control group also found antibodies in 0.2% of controls [11].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Results have been less compelling for anti-AMPAR antibodies, as the majority of studies have been negative [10, 15, 18, 20, 23, 26, 28, 29]. Moreover, in each of the two positive studies, antibodies were found in only one patient (<1% of the samples) [11, 24], and the only study that included a healthy control group also found antibodies in 0.2% of controls [11].…”
Section: Resultsmentioning
confidence: 99%
“…A number of studies that tested for IgG, IgA, or IgM anti-CASPR2 antibodies found seropositivity in a small percentage (2.5% or less) of patients [11, 15, 24, 29, 36], although numerous other studies were negative [16, 18, 20, 26, 28]. Of note, all of the positive studies that included a healthy control group, however, also found antibodies in a small number of controls (up to 2.9%), and no group differences were found [11, 15, 36].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[8][9][10] A recent case presentation of two female patients with breast cancer and paraneoplastic cerebellar disease also presenting with RBD showed clinical resolution and restoration of atonia during REM sleep after immunotherapy with intravenous immunoglobulin.…”
Section: Brief Summarymentioning
confidence: 99%
“…Likewise, sleep problems of antibody-mediated CNS disorders have often been associated with reduced cerebrospinal fluid (CSF) orexin levels [1][2][3][4]. Sleep disorders in autoimmune encephalitis have been mostly associated with Ma2, N-methyl-D-aspartate receptor (NMDAR) and leucine-rich glioma inactivated 1 (LGI1)-antibodies [1][2][3][4][5]7]. Our current knowledge on sleep disorders in antibody-mediated CNS diseases is mostly limited to case reports [1,2,7] and a systemic screening of sleep-related clinical and laboratory findings is not available.…”
Section: To the Editormentioning
confidence: 99%